(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The purpose was to evaluate effects of feeding intensity on metabolic maintenance, reproduction and welfare in blue fox vixens. Study groups were: Group 1: heavy slimming. Ad libitum feeding during September-November, aimed to produce extremely fat animals. Heavy slimming before breeding season, aim to have animals with normal breeding body condition. Group 2: maintenance of condition. Restricted feeding 35-45% from the level of Group 1 during September-November. Natural slimming to normal breeding condition. Group 3: Rising condition. Restricted feeding 50-60% from the level of Group 1 during September-November. Aim was to produce lean animals. Rising body condition was before breeding season, aimed to have animals with normal breeding body condition. Blood samples were taken regularly throughout the study. Results showed that urea concentration varied seasonally (P<0.001). Concentrations were lowest during winter period. In Group 1, heavy slimming before mating season lowered urea concentration significantly (P<0.001). During autumn period, concentration was lowest in Group 3 because of pronounced feeding restriction. Creatinine levels were highest during summer period in all groups. Glucose concentration varied seasonally in all groups (P<0.001). Intensive feeding clearly affected on triglycerides, glucose and insulin levels (P<0.01). Growth hormone (GH) and insulin-like growth factor (IGF-1) levels were highest during autumn period. Leptin concentration was highest in December in all groups. Thereafter, it clearly declined towards summer (P<0.001). Concentration of non-esterified fatty acids (NEFA) was highest in Group 1. Prolactin levels were same in all groups until insemination. During pregnancy, levels increased similarly in groups. After whelping, prolactin levels were low (P<0.05) in Group 1 compared to other groups. Whelping result in Group 1was very low (P<0.001) compared to Groups 2 and 3. It can be concluded that feeding intensity essentially influences on hormonal levels and reproduction in blue fox vixens.